Three new species of Ametrodiplosis (Diptera: Cecidomyiidae) from Japan, with a key to the Japanese species and a molecular phylogenetic analysis - Elsayed, Ayman Khamis; Yukawa, Junichi; Mochizuki, Ko; Tokuda, Makoto; Kawakita, Atsushi (Zootaxa, 2021)
Ametrodiplosis Rübsaamen (Diptera: Cecidomyiidae: Clinodiplosini) is a mostly Holarctic gall midge genus whose species are associated with a wide range of seed plant families, either as gall-inducers or inquilines. In this study, we describe three species of Ametrodiplosis from Japan: A. adetos n. sp. feeding in the flowers of Tylophora aristolochioides Miq. (Apocynaceae); A. aeroradicis n. sp. inducing aerial root galls on Trachelospermum asiaticum (Sieb. et Zucc.) Nakai and T. gracilipes var. liukiuense (Apocynaceae); and A. stellariae n. sp. forming leaf bud galls on Stellaria uliginosa Murray var. undulata (Thunb.) Ohwi (Caryophyllaceae). A molecular phylogenetic analysis using mitochondrial COI and ribosomal 16S genes and nuclear ribosomal 28S gene were conducted for the three new Ametrodiplisis species and other clinodiplosine taxa sequences available in GenBank. The analysis supported the monophyly of Ametrodiplosis despite the variable life history of the three species. In addition, it indicated very low intraspecific genetic divergence among the individuals from different localities and/or host plants. A taxonomic key to the three new Japanese species of Ametrodiplosis is provided.